In Silico Study and Bioactivity of Flavonoid Extract Syzygium polyanthum (Wight) Walp. Leaves Against Salmonella typhi - Rochmat, Agus; Hidayati, Anisa; Mujijah, Mujijah; suhaedah, suhaedah (World Chemical Engineering Journal, 2020)
Salmonella typhi bacteria cause complications of bleeding in the intestine or intestinal perforation. However, Salmonella typhi bacteria will become resistant to chloramphenicol due to the formation of plasmids that produce the chloramphenicol acetyl transferase (CAT) enzyme which works to activate chloramphenicol. So, the search for active groups of natural compounds which are expected to have the work of deactivating the CAT enzyme. One of them is a flavonoid compound. The flavonoid group is widely used as an antimicrobial. This research was aimed at the extraction of bay leaf flavonoids. The presence of flavonoids was proven by phytochemical tests, namely a yellow color change with a slightly acidic amyl alcohol solvent - Mg metal and strengthened by the scanning results of the maximum wavelength on the band 1 407 nm and band 2 338 nm which is a special feature of flavonoid backbone. The results of GC-MS analysis obtained 4 flavonoid compounds from bay leaf extract which have an abundance above 1% and qualification above 90%: 2,3-Dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one, alpha- tocopherol, beta-tocopherol, and pyragallol. The correlation between the results of the inhibitory test against Salmonella typhi at a concentration of 100 ppm with the results of docking tocopherol - 3CLA receptors which have an affinity bond energy / ∆Gbinding = 7.40 kcal / mol, indicates that the bay leaf flavonoid extract can inhibit the formation of chloramphenicol acetyl transferase (CAT).